Raconter le territoire sur la scène, dépasser les frontières par la scène - Najla Nakhlé-Cerruti (Revue des Mondes Musulmans et de la Méditerranée)
This article proposes to examine the literary, aesthetic, and performative processes encountered within a singular Palestinian theatrical production. Founded in 2015 as a transnational collective of Palestinian actors and actresses calling themselves “the Identity Lab” (huwiyya fī mukhtabar). The collective’s experience was formalized in 2017 with the staging of their first play, Other places (amākin ukhra). This vast project, begun as a reflection upon conditions peculiar to the theatre in Palestine, where mobility restrictions threaten the very survival of theatrical entertainment, whether for writing or performance. This experimental project works as a total theatrical experience from conception to live performance invoking at each stage elements specific to the creation process. It questions the conditions of life among Palestinians in their territorial context and suggests means for overcoming imposed restrictions.